DIGITALISASI PEMBUKUAN UMKM DENGAN EXCEL BERDASARKAN SAK EMKM DAN EDUKASI PPH FINAL : STUDI KASUS LAPAK SAYUR PAK DEMI SANDI - Aditya Zira Prama; Johandri Iqbal; Dwi Novrian Yuliansyah (Journal of Applied Accounting And Business, 2026)
This study examines the problem of unstructured financial recording and low tax understanding in MSMEs of Lapak Sayur Demi Sandi in Jambi Province. The absence of systematic bookkeeping causes business actors to find it difficult to know their financial condition and meet their Final Income Tax (PPh) obligations. This study aims to describe the application of bookkeeping digitization using Microsoft Excel based on Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and examine the understanding of business actors towards Final Income Tax education. The method used is descriptive qualitative research with a case study approach. Data was collected through interviews, observations, and documentation. The results of the study show that the application of Excel-based digital bookkeeping is able to improve the regularity of transaction recording and make it easier to prepare financial statements according to the EMKM SAK. In addition, Final Income Tax education increases MSME actors' understanding of tax obligations. This study concludes that digitization of bookkeeping and tax education plays a positive role in the financial management of MSMEs.